Creating comprehensive Mandarin training model for Taiwanese industry: An anticipation of Taiwan 'Southbound policy. (March 2018) - Ying, Y; Mursitama, T N; Sofi,; Anggreani, L
Abstract: The study discusses the effort of preparing human resources in mastering Mandarin for Taiwan industry as the anticipation of Southbound policy created by Taiwan government. In this point, the Southbound policy represents Taiwan's government strategy in 2016-2020 which encourages multilateral and bilateral cooperation with ASEAN and South Asian countries. One of the most important elements in the program centers as the Internship Scholarship Program in Taiwan. Utilizing qualitative research methods, researchers collected secondary data from various available official resources. The publications, documents, books, and websites contain the policy and mechanism of the internship scholarship program. On the other hand, this study conducted interviews with senior high school and vocational high school stakeholders to create synergy in the program. This study offers a model of cooperation between junior high school/vocational school and the candidates of the employer in the Taiwan industry. The contribution of this research is to create a comprehensive cooperative model that includes preparing human resources before leaving for Taiwan, providing teachers and supplying training materials that are relevant to the needs of industry players in Taiwan eventually.